The Effect of Applying TGT (Team Game Tournament) Technique to the Students’ Reading Comprehension in UMB - Erlian Dwisnu (Universitas Dehasen Bengkulu, 2022)
The using of innovative techniques in teaching reading is so useful to increase students’ achievement in reading comprehension. The students’ difficulties in comprehending the text and inactive reading class are the points of the phenomena of this research.The objective of the research was to find out and describe whether TGT technique gives positive effect to students’ reading comprehension. The research design of this research was experimental design. As the instrument of this research was reading test which consisted of 10 items essay. The result of the reading test was the TGT could increase the students’ reading comprehension ability. It can be seen after the researcher calculated by using t-test formula that t-count was higher than t-table (3.125>2.024) and the mean score of the both classes increased, 7.5 points for the control group and 18.5 points for the experimental group. So, it can be concluded that this technique gave a positive effect in teaching reading.